The Roles of Victims in the ICC: Victims’ Protection or the Accused’s Fair Trial Right Violation? - Mahfud Jufri (Faculty of Law, Hasanuddin University, 2019)
The International Criminal Court (ICC) has provided the right to present victims views in the ICC’s proceeding. The objectives of this article are to identify to which extent the roles of victims in the ICC and to analyze whether victims’ participation would be a violation to the rights of a fair trial of the accused in the ICC or not. This is pure legal research meaning that the materials required in this article are available in libraries, archives and other databases. The article concludes that the victims, in the ICC, are allowed to participate and to seek reparation in accordance with Article 68 (3) of the Rome Statute. In addition, the participation would violate the due process rights of the defendants despite the fact at a particular case; the Appeal Chamber of the ICC decided that there is no such violation as aiming at ending individual impunity.